Integrated management of seed borne pathogenic fungi of different varieties of cotton (Gossypium hirsutum L.) - Khatun, Amina; Shamsi, Shamim; Bashar, MA (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Single and combined doses of fungicides, plant extracts, and antagonists were used to control of nine cotton pathogens through a pot experiment. A total of 19 treatments, and controls with or without inocula of the pathogen were tested. Out of 19 treatments, T1 (Tilt) and T11 (Tilt + Azadirachta indica + Trichoderma viride) exhibited maximum seed germination and seedling vigor index against Aspergillus flavus, A. niger, Curvularia lunata, Fusarium nivale, Mucor sp. and A. tamarii, Colletotrichum gloeosporioides, F. moniliforme, Rhizoctonia solani respectively. T5 (T. viride), T10 (Tilt + Psidium guajava + T. viride) and T14 (Tilt + A. indica) showed promising germination percentage and seedling vigor index against A. flavus, R. solani and A. tamarii, F. nivale and A. niger, C. gloeosporioides, C. lunata, F. moniliforme, Mucor sp. respectively. Among all the treatments, the combined use of Tilt + A. indica + T. viride showed the best results for reducing the growth of the test pathogens and increasing the germination percentage of seeds. J. Asiat. Soc. Bangladesh, Sci. 49(1): 27-42, June 2023